Primary malignant CNS lymphoma in an immunocompetent patient: A case report - Khaled, A; Salauddin, SA; Zaman, SMQ; Nasir, TA (Pulse, 2011)
Aim and Objective: Primary malignant CNS lymphoma in otherwise healthy immunocompetent subject is relatively uncommon.They occur more frequently in immunocompromised patients. In this case report, we presented a report of an immunocompetent 48 year old male with primary CNS lymphoma. Clinical presentation: A 48 year old male was admitted in the neurosurgery department of Apollo hospital Dhaka because of continuous headache and vomiting for 15 days. There was no history of any illness, medication or head trauma. He was tested negative for HIV test. MRI revealed a periventricular mass which was confirmed as primary CNS lymphoma, diffuse large cell type by histopathology and immunohistochemical examination. Conclusion: We presented this case because of relatively uncommon occurrence and raising incidence of primary CNS lymphoma in immunocompetent subjects in last one or two decades. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6960 Pulse Vol.4 January 2010 p.26-27